Antepartum depressive, anxiety and comorbid symptoms among men and women in east and west coast of Malaysia: a cross-sectional analysis of a perinatal psychiatric morbidity cohort study - Nasreen, Hashima E; Ab Rahman, Jamalludin; Mohd Rus, Razman; Kartiwi, Mira; Sutan, Rosnah; Edhborg, Maigun (2018)
Introduction: Research on antepartum psychiatric morbidities investigating both depressive and anxiety symptoms in women and men is lacking in low- and middle-income countries. This study estimated the prevalence of depressive, anxiety and co-morbid symptoms and explored the associated factors in a cross-section of Malaysian pregnant women and their husbands. Methodology: The study used cross-sectional data originating from a prospective cohort study of 911 women and 587 husbands during the third trimester of pregnancy, from health clinics of two states in east and west coast of Malaysia. The validated Malay version of Edinburgh Postnatal Depression Scale, and the anxiety scale of Depression, Anxiety and Stress Scale were used to measure depressive and anxiety symptoms. Multiple logistic regression analyses identified the determinants of antepartum depressive and anxiety symptoms (ADS and AAS). Result: Prevalence of ADS was 12.2% in women and 8.4% in men, while AAS was 28.8% in women and 13.3% in men, and co-morbid symptoms was 8.0% in women and 4.0% in men. Women and men having perceived social/family support were less likely to suffer from ADS. Intimate partner violence, poor relationship with husbands, depression in earlier pregnancy and husband’s depression in current pregnancy in women, and living in rented house, sex preference for the unborn child, stressful life events and wife’s depression in current pregnancy in men were associated with a greater likelihood of ADS. The determinants for AAS were living in rented house and with parents/in-laws, poor relationship with husbands, restrictions during pregnancy and stressful life events for women, and stressful life events and being unsupported towards wives in household chores for men. Conclusion: Depressive and anxiety symptoms during pregnancy are prevalent in women and men, and largely an undetected problem in Malaysia. Administration of couple-based screening and referral programme during antenatal check-up should be universal practices to identify and treat the psychiatric morbidities.